Cooperative dihydrogen activation at a Na(i)2/Mg(i)2 ensemble. Issue 26 (8th March 2023) - Liu, Han-Ying; Neale, Samuel E.; Hill, Michael S.; Mahon, Mary F.; McMullin, Claire L.; Morrison, Benjamin L.
Abstract : [SiN Dipp MgNa]2 (SiN Dipp = CH2 SiMe2 N(Dipp)2 ; Dipp = 2, 6-i-Pr2 C6 H3 ) reacts directly with H2 in a process, which computational studies suggest, is dictated by the frontier MOs of both H2 and the low oxidation state s-block assembly. Abstract : [SiN Dipp MgNa]2 (SiN Dipp = CH2 SiMe2 N(Dipp)2 ; Dipp = 2, 6-i-Pr2 C6 H3 ) reacts directly with H2 to provide a heterobimetallic hydride. Although the transformation is complicated by the simultaneous disproportionation of magnesium, computational density functional theory (DFT) studies suggest that this reactivity is initiated by orbitally-constrained and interactions between the frontier MOs of both H2 and the tetrametallic core of [SiN Dipp MgNa]2 .